Development Of Strategies Business Plan For A Small Construction Firm: A Case Study On Tricomtec Sdn Bhd. - Chin, Tee Li (2004)
Tricomtec Sdn, Bhd, a small construction firm located at Sri Damansara, Kuala Lumpur is selected as the case in the research study. This study discusses literature related to the past and current practice of construction industry, as well as the review of the strategies suggested by the past researcher.The findings should help the small entrepreneurs understand at which combined levels of historical performance and resource avaolability are growth, retrenchment or stability strategies most appropriate.